The Relationship between Mental and Somatic Practices and Wisdom. - Patrick B Williams; Heather H Mangelsdorf; Carly Kontra; Howard C Nusbaum; Berthold Hoeckner (PLoS ONE, 2016)
In this study we sought to explore how experience with specific mental and somatic practices is associated with wisdom, using self-report measures of experience and wisdom. We administered standard surveys to measure wisdom and experience among four groups of practitioners of mental and somatic practices, namely, meditators, practitioners of the Alexander Technique, practitioners of the Feldenkrais Method, and classical ballet dancers. We additionally administered surveys of trait anxiety and empathy to all participants to explore possible mediating relationships of experience and wisdom by characteristics thought to be components of wisdom. Wisdom was higher on average among meditation practitioners, and lowest among ballet dancers, and this difference held when controlling for differences in age between practices, supporting the view that meditation is linked to wisdom and that ballet is not. However, we found that increased experience with meditation and ballet were both positively associated with wisdom, and that lowered trait anxiety mediated this positive association among meditation practitioners, and, non-significantly, among ballet dancers. These results suggest that not all practices that are purported to affect mental processing are related to wisdom to the same degree and different kinds of experience appear to relate to wisdom in different ways, suggesting different mechanisms that might underlie the development of wisdom with experience.